Two new synonyms of Ormosia semicastrata (Fabaceae, Papilionoideae, Ormosieae) - Niu, Miao; Jiang, Kai-Wen; Song, Zhu-Qiu; Duan, Lei; Tu, Tie-Yao; Li, Shi-Jin (Phytotaxa, 2023)
Based on the examination of herbarium specimens and observations of the living plants in the wild, Ormosia apiculata H. Y. Chen and O. howii Merr. & Chun ex Merr. & H. Y. Chen, are considered conspecific with O. semicastrata Hance, a species widely distributed in southern China. Here we synonymized O. apiculata and O. howii under O. semicastrata.